Gestational syphilis: difficulty in adhering to treatment from the nursing professional’s perspective - Silva, Francisca Mayara Gabriel da; Santos, Rita de Cássia Pereira; Quental, Ocilma Barros de; Oliveira, Rafaela Rolim de; Macena, Luiz Felipe da Costa; Felix, Maria Eduarda Batista; Rolim, Maria Lariel Lopes; Feitosa, Ankilma do Nascimento Andrade (Brazilian Journal of Production Engineering, 2023)
Introduction: Syphilis is an infectious and systemic disease, caused by the etiological agent Treponema pallidum. When not treated during pregnancy, it can affect the fetus, causing serious health risks. Objective: To describe the difficulties of adherence to the treatment of gestational syphilis from the perspective of nursing professionals. Methodology: This was a descriptive research, with a quantitative approach, of the field research type, data collection took place in 20 Family Health units, located in the municipality of Cajazeiras-PB, in April 2023. Nursing professionals who have provided assistance to pregnant women with syphilis were included in the study. The information obtained was processed and analyzed in SPSS (version 26). Results: The present study showed through 15 nurses that (80%) of the pregnant women started prenatal care in the first trimester, and (20%) presented complications due to gestational syphilis, and (60%) of the partners do not perform the treatment. Conclusion: Through this study, it is observed that for the treatment to be effective, it is necessary to treat the partner about syphilis so that relapse does not occur, that nursing professionals together with the multidisciplinary team of the FHS seek to improve in terms of management clinical syphilis.